COMBINE GAME THEORY AND AHP TO CHOOSE STRATEGIC ORIENTATION IN TECHNOLOGY DEVELOPMENT - INDONESIAN CASE - Ilham Said (Jurnal Teknik Industri: Jurnal Keilmuan dan Aplikasi Teknik Industri, 2002)
The objective of this paper is to give direction to the three main economic players (industry, government and academician) in determining their strategic orientation in technology development. The model will be built in interactive framework where in making decision each player considers other possible strategic choices. A three-dimension game theory combined with an interactive decision structural model of Analytical Hierarchy Process (AHP) will be used to find the solution. The results reveal that collaboration strategy give the highest outcome for the three players. It recommends industry and academician to make collaboration in undertaking innovation while the government should let an independent organization to manage technology development.